De paarse peperpot : tweemaandelijks infoblad. (Brussel : Paarse Peperpot, 1986)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Rijkeklarenstraat 14-18, 1000 Brussel ; vanaf (1987) 5 : p/a TILT, Grétrystraat 26, 1000 Brussel ; vanaf (1987) 6 : p/a ‘Het volwassen antwoord’, Oude Graanmarktstraat 39, 1000 Brussel
Nederlands
Periodiek